THE INFLUENCE OF HEALTH EDUCATION ABOUT PLASTIC CODES ON THE USE OF PLASTIC CONTAINERS IN HOUSEWIVES - Yenni Farida Siregar; Nur Aliyah Rangkuti; Fahrizal Alwi (Jurnal Kesehatan Medika Saintika, 2020)
The use of plastic is quite popular among the people. Most of the housewives use plastic as a container for food and drinks in their daily life. This is because plastics have superior properties such as being strong but light, not rusting, being thermoplastic, which can be bonded using heat. However, behind the advantages of plastic, there are also disadvantages of plastic, including it is not heat resistant, is toxic and can cause health problems. This study aims to analyze the effect of health education on plastic codes on the use of plastic containers among housewives. This type of research is a quantitative study with a quasi-experimental design through a one group pre-test post-test approach. The number of samples in this study were 43 people with total sampling technique. The analysis to be carried out is the paired two-sample Wilcoxon test to test the mean difference in the pre-post design, with a confidence level of 95% (α ≤ 0.05). The results showed the distribution of the use of plastic containers prior to the health education intervention (pretest), there were 38 respondents (88.4%) who did not use plastic containers according to the code and 5 respondents (11.6%) who used plastic containers according to the code. After the health education intervention there were 12 respondents (27.9%) who did not use plastic containers according to the code and 31 respondents (72.1%) who used plastic containers according to the code, this means that the use of plastic containers for respondents after being given health education has increased. . The results of the Wilcoxon test can be concluded that there is an effect of health education on the use of plastic containers for housewives (p-value = 0.000 <α = 0.05). With the results of this research, it is hoped that it will be able to increase the insight of housewives to be more careful in choosing a container to be used as a place for food and drinks to prevent health problems and be an initial step in improving the health status of families and communities.